2020
DOI: 10.3389/fmolb.2020.604252
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Model of Colorectal Cancer Constructed by Eight Immune-Related Genes

Abstract: BackgroundColorectal cancer (CRC) is a common malignant tumor of the digestive tract with a high mortality rate. Growing evidence demonstrates that immune-related genes play a prominent role in the occurrence and development of CRC. The aim of this study was to investigate the prognostic value of immune-related genes in CRC.MethodsGene expression profiles and clinical data of 568 CRC and 44 non-tumorous tissues were obtained from The Cancer Genome Atlas (TCGA) database. First, we performed a differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The AUC at 1 year OS was compared between the IRGs signature and three published IRGs signatures, which included an 8-gene signature (Wen IRGSig), a 6-gene signature (ZhangIRGSig), and a 5-gene signature (Zhu IRGSig) in the same TCGA cohort ( Zhang et al, 2020b ; Wen et al, 2020 ; Zhu et al, 2020 ). The AUC of the IRGs signature at 1-year OS was 0.774, which was the highest of that of Wen IRGSig (0.640), ZhangIRGSig (0.720), and Zhu IRGSig (0.620) ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The AUC at 1 year OS was compared between the IRGs signature and three published IRGs signatures, which included an 8-gene signature (Wen IRGSig), a 6-gene signature (ZhangIRGSig), and a 5-gene signature (Zhu IRGSig) in the same TCGA cohort ( Zhang et al, 2020b ; Wen et al, 2020 ; Zhu et al, 2020 ). The AUC of the IRGs signature at 1-year OS was 0.774, which was the highest of that of Wen IRGSig (0.640), ZhangIRGSig (0.720), and Zhu IRGSig (0.620) ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have reported that DMGs and DEGs can be used as prognostic and diagnostic biomarkers for CRC [11,[28][29][30]. A previous study also reported that MDGs can assist with determining the prognosis of CRC patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies highlight the role of the microbiota composition in intestinal inflammation in mice and humans, which has been linked to colorectal cancer 56 . There have been many publications and studies on the risk prediction model for the prognosis of colon cancer based on immune genes 57 62 . The abnormal metabolism of tumor glucose and lipids is an important part of tumor metabolic reprogramming, which is closely related to tumor occurrence, development, and prognois 50 .…”
Section: Discussionmentioning
confidence: 99%